Penerapan Metode Profile Matching dalam Menentukan Sunscreen Terbaik Bagi Kulit Berminyak Berdasarkan Konsumen - Anggie Zahrawani; Auliya Ul Husna; Amanda Agustria; Surya Darma (Journal of Information System Research (JOSH), 2025)
Exposure to ultraviolet (UV) rays from the sun can have negative effects on skin health, especially for individuals with oily skin who are prone to acne and irritation. This study aims to apply the profile matching method in determining the most suitable sunscreen for consumers with oily skin. The large number of skin care products on the market makes it difficult for consumers to choose the right product for their skin needs. This study aims to apply the profile matching method in recommending skin care products that are suitable for consumers with oily skin. The profile matching method is used to match consumer skin characteristics with skin care product specifications based on certain parameters, such as oil level, skin sensitivity, and desired effects. Data was obtained through surveys and direct testing of consumers with oily skin types. The results of the study show that the application of the profile matching method provides more suitable and satisfying product recommendations for consumers. Based on the research conducted, it was found that the best sunscreens for oily skin are, in order, Wardah with a total score of 2.045, followed by Facetology in second place with a total score of 1.991, then Azarine and The Originote with identical total scores of 1.975, and finally Skintific with a total score of 1.891. The results of this study serve as recommendations for customers.